REGULASI PRODUK: UPAYA, INOVASI PEMERINTAH DALAM MEMINIMALISIR KELANGKAAN PUPUK DALAM PRESPEKTIF ISLAM DI KABUPATEN PROBOLINGGO - Fauzan Firmansyah; Mohammad Syaiful Su’ib (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
In an effort to increase the effectiveness of implementing the subsidized fertilizer distribution system policy, it is necessary to improve policies covering technical, management and regulatory aspects. Technical aspects: (a) increasing the intensity of dissemination of site-specific balanced fertilization systems and the use of organic fertilizers, (b) accelerating the development of organic fertilizers. Management Aspects: (a) closed socialization of the subsidized fertilizer distribution system to stakeholders including government officials, community leaders and farmers, (b) cross-sectoral coordination to ensure the effectiveness of subsidized fertilizer distribution and implementation of fertilization, and (c) repositioning of fertilizer distribution kiosks in Line IV by increasing the role of local governments in regulating the supply and distribution of subsidized fertilizers. Regulatory Aspects: (a) RDKK should be used as a 'node' that connects Permendag No. 21/M-DAG/PER/6/2008 and Minister of Agriculture No. 42/Permentan/OT.140/09/2008, and (b) fertilizer need allocation planning based on RDKK needs to be followed by distribution based on RDKK.